2008
DOI: 10.1007/s00198-007-0525-7
|View full text |Cite
|
Sign up to set email alerts
|

Secondary contributors to bone loss in osteoporosis related hip fractures

Abstract: Osteoporosis treatment of HFx is necessary to prevent subsequent fractures. Secondary causes for bone loss are remarkably common in HFx; therefore, assessment of vitamin D status, disorders in calcium absorption and excretion, protein electrophoresis, and renal function should be performed. Identifying and correcting these disorders will improve detection and enhance treatment aimed at reducing the risk of recurrent fractures in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 66 publications
2
42
0
Order By: Relevance
“…Uncertainty about the cut-points was presented in only four of 92 visits (4.3 %). One [18][19][20][21][22][23][24] -There is inadequate evidence linking vitamin D to health outcomes such as immune disease, cardiovascular disease, cancer risk, quality of life 15 Presenting benefits of vitamin D that are not fully substantiated in the literature Certain statements BThe thing about vitamin D that's so amazing is…it works on cancer. It works on heart disease.…”
Section: Comparison Of Provider Discussion and Scientific Evidence mentioning
confidence: 99%
“…Uncertainty about the cut-points was presented in only four of 92 visits (4.3 %). One [18][19][20][21][22][23][24] -There is inadequate evidence linking vitamin D to health outcomes such as immune disease, cardiovascular disease, cancer risk, quality of life 15 Presenting benefits of vitamin D that are not fully substantiated in the literature Certain statements BThe thing about vitamin D that's so amazing is…it works on cancer. It works on heart disease.…”
Section: Comparison Of Provider Discussion and Scientific Evidence mentioning
confidence: 99%
“…Secondary causes for bone loss are remarkably common in patients with hip fractures, as Edwards et al [17] found more than 80% of patients with hip fractures had an unrecognized cause for bone loss, with vitamin D deficiency being most common. Osteoporosis in men is more likely to be a marker of a systemic disease.…”
Section: Pathophysiology Of Osteoporosismentioning
confidence: 99%
“…4 Results from other published studies on fractures in MGUS patients [5][6][7][8] have shown 1.4-to 6.3-fold increased risk of fractures in MGUS patients. Researchers have found a high prevalence of MGUS in osteoporotic patients, [9][10][11][12] which has led some authors to suggest that protein electrophoresis should always be performed as screening for MGUS (and MM) in patients with osteoporosis and/or fractures. 9,10,13 However, these studies have been limited by lack of control population, and the scientific rationale for these recommendations is scarce.…”
Section: Introductionmentioning
confidence: 99%